Athens and Jerusalem, The University and Religious Counselling - Shea, Edward C. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper examines the relationship between the secular university and religion with special reference to religious counselling. The contentionis that there is a new spirit of cooperation between the university and religion and that there is thus a need for a chaplain's presence on the campus. There is an examination of the kinds of counselling that achaplain does. The paper concludes with some suggestions for the religious denominations as they relate to the academic community.